Development of a New Polar Organic Chemical Integrative Sampler for 1, 4‐dioxane Using Silicone Membrane as a Diffusion Barrier. (16th December 2022) - Noro, Kazushi; Endo, Satoshi; Inoue, Daisuke; Suzuki, Natsumi; Kameoka, Hiroshi; Ono, Junko; Nakamura, Satoshi; Yabuki, Yoshinori
Abstract: Efficient monitoring methods must be developed for 1, 4‐dioxane, which is suspected to be carcinogenic to humans and is highly mobile in aquatic environments. In this regard, polar organic chemical integrative samplers (POCIS) have been utilized extensively as passive samplers for determining time‐weighted average concentrations of hydrophilic organic compounds. However, POCIS are difficult to apply to extremely hydrophilic known organic compounds with negative log octanol–water partition coefficient ( K ow ) values due to their limited kinetic sampling time. Using an activated carbon‐based sorbent with a high adsorption capacity and a bilayer of silicone and polyethersulfone membranes that inhibit mass transfer to the sorbent, we developed a POCIS device to measure 1, 4‐dioxane (log  K ow −0.27) in the present study. Permeation and field calibration tests demonstrated that the use of silicone membranes effectively reduces the water‐to‐sorbent mass transfer rate. The sampling rate and kinetic sampling period determined by field calibration tests were 1.4 ml day −1 and >14 days, respectively. Finally, the developed POCIS device was applied to a landfill treatment plant to determine the 1, 4‐dioxane concentrations. Environ Toxicol Chem 2023;42:296–302. © 2022 SETAC